Academic coaching as a pedagogy to facilitate the navigation of complexity across the health professions education continuum - King, Svetlana M.; Carnicer Hijazo, Ricardo; Anas, Shafeena; Low-Beer, Naomi (Frontiers in Medicine, 2025)
Maintaining currency and managing complexity in a rapidly evolving healthcare environment requires health professionals to be competent in monitoring and regulating their own learning. While health professional educators can scaffold learners to develop this competency, maintaining these skills in the absence of ongoing, structured support can prove challenging. Academic coaching is a pedagogical approach that supports learners to develop as self-regulated learners. This longitudinal support can facilitate learners’ capacity to plan, monitor and evaluate their performance and apply these skills to novel contexts, which is needed to navigate the increasingly complex healthcare environment. In this paper, we introduce the intersecting concepts of self-regulated learning and academic coaching. We suggest ways that academic coaching can be used to support learners in the health professions to continually improve their practice and develop their capacity to cope with complexity. We draw on our experiences of implementing academic coaching into two medical programs in the UK and Australia (school-leaver and graduate entry programs, respectively) and offer considerations for implementing academic coaching across the health professions education continuum.